Black-Banded Honey Bee, Sulawesian Honey Bee Apis nigrocincta Smith (Insecta: Hymenoptera: Apidae) - Lisa Rodriguez; Brynn Johnson; Cameron Jack (EDIS)
The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. Apis nigrocincta Smith (1860) is a cavity-nesting honey bee native to the Philippines and Indonesia. The Florida Department of Agriculture and Consumer Services – Division of Plant Industry’s Apiary Inspection Section is actively screening for invasive honey bee species in an effort to eradicate unwanted pests. This bee is not currently considered a threat to Florida, but state researchers are actively screening honey bees of unknown origins using molecular markers to detect the presence of Apis nigrocincta.